2000
DOI: 10.1109/16.841241
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the MIC/MILC interface and its effects on the performance of MILC thin-film transistors

Abstract: Abstract-Process and material characterization of the crystallization of amorphous silicon by metal-induced crystallization (MIC) and metal-induced lateral crystallization (MILC) using evaporated Ni has been performed. An activation energy of about 2 eV has been obtained for the MILC rate. The Ni content in the MILC area is about 0.02 atomic %, significantly higher than the solid solubility limit of Ni in crystalline Si at the crystallization temperature of 500 C. A prominent Ni peak has been detected at the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Low-temperature crystallization processes of the poly-Si channel films have been studied extensively, including solid-phase crystallization (SPC), laser crystallization (LC) and metal-induced lateral crystallization (MILC) 1416 . The MILC method has a metal contamination issue in the poly-Si channel, resulting in the degradation of the junction leakage.…”
Section: Resultsmentioning
confidence: 99%
“…Low-temperature crystallization processes of the poly-Si channel films have been studied extensively, including solid-phase crystallization (SPC), laser crystallization (LC) and metal-induced lateral crystallization (MILC) 1416 . The MILC method has a metal contamination issue in the poly-Si channel, resulting in the degradation of the junction leakage.…”
Section: Resultsmentioning
confidence: 99%
“…Although poly-Si films can be synthesized by a direct deposition method from a gas phase, [16][17][18] the preferred fabrication method is the crystallization of an amorphous precursor, which results in a higher mobility due to a larger grain size and a lower crystalline defect density. The crystallization of deposited a-Si films can be carried out by several methods, such as solid phase crystallization (SPC), [19][20][21][22][23] metal-induced crystallization (MIC), [24][25][26][27] metalinduced lateral crystallization (MILC), [28][29][30][31] and pulsed laser annealing (PLA). [32][33][34][35] Among them, PLA has become a leading technique used to fabricate poly-Si films at low temperatures because its melt-crystallized films have large grains with high mobilities.…”
Section: Introductionmentioning
confidence: 99%
“…4 In most published work, the Ni is defined either by a lift-off process [5][6][7][8][9] or by Ni deposition in a window opened in a cap layer, which is normally deposited silicon dioxide.…”
mentioning
confidence: 99%
“…1 For MILC, nickel reacts with amorphous silicon (α-Si) to form nickel disilicide and the lateral transport of Ni induces crystallization of the adjacent amorphous silicon, 2,3 creating a crystallized region with low Ni contamination suitable for high performance transistors. 4 In most published work, the Ni is defined either by a lift-off process [5][6][7][8][9] or by Ni deposition in a window opened in a cap layer, which is normally deposited silicon dioxide. [10][11][12][13][14][15] So far, no work has been reported that compares the effect of these two different Ni definition techniques on the lateral crystallization.…”
mentioning
confidence: 99%